Analisis Disiplin Kerja Karyawan Pada CV XYZ Bogor - Firmansyah Firmansyah; Awa Awa (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Work discipline plays a crucial role in enhancing operational efficiency and organizational performance, particularly in service-based industries where coordination and timeliness are essential. In the event organizer sector, employee discipline directly influences service quality and client satisfaction. This study aims to examine the implementation of employee work discipline at CV XYZ Bogor, a company operating in the Event Organizer service sector. The research employs a qualitative approach with a case study design to obtain an in-depth understanding of actual workplace conditions. Data were collected through field observations, interviews with management and employees, and analysis of relevant organizational documents. The participants consisted of all 20 employees, allowing for a comprehensive representation of the company’s internal dynamics. The findings indicate that the implementation of work discipline has not been fully effective. This is reflected in inconsistent punctuality, limited adherence to standard operating procedures, varying levels of responsibility in task completion, and suboptimal use of work facilities. These results highlight the need to strengthen discipline management through enhanced supervision, exemplary leadership, and consistent enforcement of organizational regulations. This study contributes to human resource management literature, particularly within the creative service industry, and provides practical recommendations for improving employee discipline practices.